LIMK (LIM Kinase) Inhibition Prevents Vasoconstriction- and Hypertension-Induced Arterial Stiffening and Remodeling. Issue 2 (August 2020) - Morales-Quinones, Mariana; Ramirez-Perez, Francisco I.; Foote, Christopher A.; Ghiarone, Thaysa; Ferreira-Santos, Larissa; Bloksgaard, Maria; Spencer, Nicole; Kimchi, Eric T.; Manrique-Acevedo, Camila; Padilla, Jaume; Martinez-Lemus, Luis A.
Abstract : Increased arterial stiffness and vascular remodeling precede and are consequences of hypertension. They also contribute to the development and progression of life-threatening cardiovascular diseases. Yet, there are currently no agents specifically aimed at preventing or treating arterial stiffening and remodeling. Previous research indicates that vascular smooth muscle actin polymerization participates in the initial stages of arterial stiffening and remodeling and that LIMK (LIM kinase) promotes F-actin formation and stabilization via cofilin phosphorylation and consequent inactivation. Herein, we hypothesize that LIMK inhibition is able to prevent vasoconstriction- and hypertension-associated arterial stiffening and inward remodeling. We found that small visceral arteries isolated from hypertensive subjects are stiffer and have greater cofilin phosphorylation than those from nonhypertensives. We also show that LIMK inhibition prevents arterial stiffening and inward remodeling in isolated human small visceral arteries exposed to prolonged vasoconstriction. Using cultured vascular smooth muscle cells, we determined that LIMK inhibition prevents vasoconstrictor agonists from increasing cofilin phosphorylation, F-actin volume, and cell cortex stiffness. We further show that localized LIMK inhibition prevents arteriolar inward remodeling in hypertensive mice. This indicates that hypertension is associated with increased vascular smooth muscle cofilin phosphorylation, cytoskeletal stress fiber formation, and heightened arterial stiffness. Our data further suggest that pharmacological inhibition of LIMK prevents vasoconstriction-induced arterial stiffening, in part, via reductions in vascular smooth muscle F-actin content and cellular stiffness. Accordingly, LIMK inhibition should represent a promising therapeutic means to stop the progression of arterial stiffening and remodeling in hypertension. Abstract : Supplemental Digital Content is available in the text.